Long non‐coding RNAs in rheumatoid arthritis - Li, Zheng; Li, Xingye; Jiang, Chao; Qian, Wenwei; Tse, Gary; Chan, Matthew T.V.; Wu, William K.K. (Cell proliferation, 2018)
Rheumatoid arthritis, a disabling autoimmune disease, is associated with altered gene expression in circulating immune cells and synovial tissues. Accumulating evidence has suggested that long non‐coding RNAs (lncRNAs), which modulate gene expression through multiple mechanisms, are important molecules involved in immune and inflammatory pathways. Importantly, many studies have reported that lncRNAs can be utilized as biomarkers for disease diagnosis and prognostication. Recently, dysregulation of lncRNAs in rheumatoid arthritis and other autoimmune diseases has been revealed. Experimental studies also confirmed their crosstalk with matrix metalloproteinases, nuclear factor‐κB signalling and T‐cell response pertinent to autoimmunity and inflammation. Circulating lncRNAs, such as HOTAIR, differentiated patients with rheumatoid arthritis from healthy subjects. Taken together, lncRNAs are good candidates as biomarkers and therapeutic targets in rheumatoid arthritis. Further investigation on in vivo delivery of these regulatory molecules and large‐cohort validation of their clinical applicability may be useful.